KEBIJAKAN LUAR NEGERI AMERIKA SERIKAT TERHADAP COUNTER TERRORISM PADA MASA KEPEMIMPINAN OBAMA - Jamil, Arya Hamsul; Rani, Faisyal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
In November 2009, Barack Obama inaugurated as the 44th US President switching the George W. Bush leadership in US. In his leadership, Obama declared to continue the GWOT (Global War on Terror) Bush strategy to counter the terrorism. The big differences between Obama GWOT and Bush is the on his order to closed the Guantanamo jail and to drag all US troops from Iraq. Many criticized the tariffs as a protectionist move by the China, because in recent years, the United States placed tariffs on one China infant industry with same reason. The focus of this research is to analyze the real motif China placed tariff on broiler chicken product from U.S. Are this have any reason connected to U.S placed tarif on China infant industry. This research uses Llyod Jensen - the Decision Making Theory related to individual level analysis which concern to leadership behavior as an effective element in decision making process and determining foreign policy. This research is Qualitative research which is used by library observation. The result of this research prove that there’s several factor that determining Obama decision making process on counter-terrorism. In Obama GWOT focus the invasion on Pakistan and Afghanistan switching the war on Iraq and Afghanistan. Bush so much influenced by the used of military forced against Al-Qaeda, while Obama bringing a concept of Smart Power using by the blend of hard and soft power.Keywords: Foreign Policy, Global War on Terror, Smart Power